2014
DOI: 10.2478/agri-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage System and Soil Conditioner Application on Soybean (Glycine Max (L.) Merrill.) and Its Crop Management Economic Indicators

Abstract: Effect of tillage system and soil conditioner application on soybean (Glycine max (L.) Merrill.) and its crop management economic indicators. Agriculture (Poľnohospodárstvo), vol. 60, 2014, no. 2, pp. 60-69. Ing. Ladislav Kováč, PhD. (*Corresponding author), National Agricultural and Food Centre, Research Institute of Agroecology, 071 01 Michalovce, Špitálska 1273, Slovak Republic. E-mail: kovac@minet.sk Key words: soybean, fertilisation, soil tillage, costs, economic effectiveness 60 Agriculture (Poľnohos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…The evolution of soybean production in Transylvania has been directly influenced by annual climate variations in the research area. The same conclusion has been reported by studies on other areas where soybean is cultivated [19].…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…The evolution of soybean production in Transylvania has been directly influenced by annual climate variations in the research area. The same conclusion has been reported by studies on other areas where soybean is cultivated [19].…”
Section: Introductionsupporting
confidence: 89%
“…Similar to our results of favorable ecological conditions for soybean production, a study Turkey by [45] determined that the highest yield from a conventional system (2036 kg ha −1 ) was comparable to the yield with reduced tillage (2015 kg ha −1 ) with a difference of only 21 kg ha −1 , and a low yield with a no tillage system (1881 kg ha −1 ). Similar results were obtained by a study from 2010 to 2012 with soybeans on heavy soil (the content of clay more than 53%) in East Slovakia [19]. They studied the effect of three tillage systems (conventional, minimum tillage, and no tillage) and reported that the higher yields were achieved with conventional and minimum tillage variants, with no significant difference in the yield between these variants, but the soybean yield in the no tillage variant was significantly lower.…”
Section: Tillage and Soybean Yieldsupporting
confidence: 74%
See 1 more Smart Citation
“…PRP SOL can also replace the inorganic fertilizing of spring barley with phosphorus and potassium without grain yield losses [51]. Another study [52] of a two-year soybean experiment did not show any statistically significant increase in yields when using the SOL activator. Conversely, PRP SOL in combination with urea was found to have a positive effect in terms of increased soybean yield [19].…”
Section: Discussionmentioning
confidence: 99%
“…Under field conditions, soil moisture content during winter may vary in time and space depending on rainfall amount, microtopography (Bo et al ., ), soil depth (Qiu et al ., ), tillage (Kováč et al ., ) and irrigation management (Kang et al., ). Moreover, climate change also may alter soil moisture conditions, thus affecting seed dormancy release and consequently seedling recruitment and community composition (Walck et al ., ).…”
Section: Introductionmentioning
confidence: 99%